Communal Property Rights and Depletion of Forests in Northern Pakistant (The Pakistan Development Review, 1989)
This paper argues that the causes of rapid depletion of forests in Northern Pakistan are to be found not only in an extensive admission of open-ended communal prope.rty rights, but also an inadequate specification of those rights. Central to the problem are guzara forests. It is these forests for which property rights have, at best, been inadequately defined. It is true that at the time the rights in these forests were admitted in the last half of the past century, the prevailing conditions were vastly different, and the admission of rights did not seem to pose a serious conservation threat. As the rights became well-entrenched with the passage of time, the state has found it increasingly difficult to affect any changes in their structure for the sake of conservation. The equany important problem of inadequate specification of those rights has remained unnoticed. The paper looks at the evolution of the forementioned rights in three adjacent forest divisions; Murree Kahuta (M-K) in the province of Punjab; and Jlaripur and Galis (H&G) in the North West Frontier Province (NWFP), that cover an important part of the lower watershed area of the rivers Indus and Jhelum. This account in Section IV of the paper, in the background of brief overviews of property rights in Pakistan's forests, and the theory of property rights in Sections II, and III respectively leads to certain policy relevant conclusions in Section V.